Dissecting FOXP2 Oligomerization and DNA Binding. Issue 23 (29th April 2019) - Häußermann, Katharina; Young, Gavin; Kukura, Philipp; Dietz, Hendrik
Abstract: Protein–protein and protein–substrate interactions are critical to function and often depend on factors that are difficult to disentangle. Herein, a combined biochemical and biophysical approach, based on electrically switchable DNA biochips and single‐molecule mass analysis, was used to characterize the DNA binding and protein oligomerization of the transcription factor, forkhead box protein P2 (FOXP2). FOXP2 contains domains commonly involved in nucleic‐acid binding and protein oligomerization, such as a C2 H2 ‐zinc finger (ZF), and a leucine zipper (LZ), whose roles in FOXP2 remain largely unknown. We found that the LZ mediates FOXP2 dimerization via coiled‐coil formation but also contributes to DNA binding. The ZF contributes to protein dimerization when the LZ coiled‐coil is intact, but it is not involved in DNA binding. The forkhead domain (FHD) is the key driver of DNA binding. Our data contributes to understanding the mechanisms behind the transcriptional activity of FOXP2. Abstract : It takes two to tango : A combined biochemical and biophysical approach based on electrically switchable DNA biochips and single‐molecule mass analysis was used to unravel the key contributors to DNA binding and protein oligomerization of the forkhead box protein P2 (FOXP2), which is a human transcription factor, important for language and speech development.